2016
DOI: 10.1088/0957-4484/27/14/144001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of surface charge state on the surface stress of a microcantilever

Abstract: The surface charge state at a liquid-solid interface is important to the variations in the physical/chemical properties of adsorbate film such as surface stress and the ensuing tip deflection of the microcantilever. The well-known Stoney's equation, derived more than 100 years ago, conceals the film electrical properties with the replacement of substrate deformation induced by adsorptions of particles. This implicit expression provides a shortcut to circumvent the difficulty in identifying some film properties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 53 publications
2
9
0
Order By: Relevance
“…However, like many other sensors within real-life biofluid environments, nonspecific adsorption is still the main technical obstacle to overcome if microcantilever-based biodetection were to succeed in practical conditions. As recent studies demonstrated, the reproducibility of the microcantilever-based biosensors can be improved as the surface charge and stress states of biofluid-microcantilever interfaces are better understood . Furthermore, the sensitivity of microcantilever sensors can be enhanced by integration or combination with other detection schemes, such as SPR, to create opto-mechanical hybrid sensors …”
Section: Examples Of Nanostructured Biomolecular Detectorsmentioning
confidence: 99%
“…However, like many other sensors within real-life biofluid environments, nonspecific adsorption is still the main technical obstacle to overcome if microcantilever-based biodetection were to succeed in practical conditions. As recent studies demonstrated, the reproducibility of the microcantilever-based biosensors can be improved as the surface charge and stress states of biofluid-microcantilever interfaces are better understood . Furthermore, the sensitivity of microcantilever sensors can be enhanced by integration or combination with other detection schemes, such as SPR, to create opto-mechanical hybrid sensors …”
Section: Examples Of Nanostructured Biomolecular Detectorsmentioning
confidence: 99%
“…First, based on a macroscopic piezoelectric theory, an analytical relation between the cantilever deflection and the electric potential of the adsorbate film is recited here as in the previous works [21], where the adsorbate film was viewed as a kind of piezoelectric materials [16], while the substrate was treated as an elastic material.…”
Section: Multiscale Prediction For Piezoelectric Coefficient Of Dna Filmmentioning
confidence: 99%
“…As for the cantilever deformation, it could be obtained by the energy approach. The Hamiltonian for the adsorbate film is given as [21]…”
Section: Multiscale Prediction For Piezoelectric Coefficient Of Dna Filmmentioning
confidence: 99%
See 2 more Smart Citations